First clinical experience with the wearable cardiac rhythm long-term monitoring cardioskin device. (25th November 2020) - Guedeney, P; Silvain, J; Hidden-Lucet, F; Maupain, C; Dinanian, S; Waintraub, X; Gandjbakhch, E; Montalescot, G
Abstract: Background: There are only limited options for long-term cardiac monitoring devices readily available in clinical practice for outpatients. Holter monitoring devices are limited by the uncomfort of wires and patches, the small number of leads for analysis, the quality of recordings or the monitoring duration while insertable cardiac monitors are costly and exposed to potential local complication. Purpose: To describe a single center experience with a novel wearable device for cardiac rhythm monitoring. Methods: The Cardioskin™ system is a patch-free, wire-free, wearable device with rechargeable batteries that provides a high quality 15-lead electrocardiogram monitoring over 1 month (Figure 1). Data are sent using a mobile application downloaded in the patient smartphone to a central Corelab where they can be interpreted by an expert and/or the prescribing physician. An alarm signal is readily available within the Cardioskin™ device, to allow patients to indicate the presence of symptoms. In this single center retrospective registry, we provide a first report of the use of this novel device in real world practice, with indication and duration of cardiac monitoring left at the physicans "discretion". Results: From January 2019 to December 2019, the Cardioskin™ system was prescribed in 60 patients for an overall median duration of 26.5 (14–32) days. The mean age of the patients was 45±12.2 years and 24 (40%) were male. Indications for cardiac monitoring were post-Stroke, palpitation, syncope and cardiomyopathy assessment in 56%, 30%, 7% and 7% of the cases, respectively. A sustained (>30 seconds) supraventricular tachycardia was detected in 4 cases, including one case of atrial fibrillation, two case of atrial tachycardia and on case of junctional tachycardia. Unsustained ventricular tachycardia and atrial fibrillation burst were detected in another 2 cases (Figure 1). There was no reported case of skin irritation by the Cardioskin™ system or abrupt interruption of the monitoring by the patients. Conclusion: The Cardioskin™ system is a novel, discreet and comfortable cardiac rhythm wearable long-term monitoring device which can be used in clinical practice for broad diagnostic indications. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): ACTION coeur